Age and gender distribution of pterygium cases from the pterygium surgery social service program - Supanji Supanji; Tania Purbonegoro; Anindita Dianratri; Krisna Dwi Purnomo Jati; Agung Saputro; Aloysius Angga Wibowo; Suhardjo Suhardjo (Journal of Community Empowerment for Health, 2021)
Pterygium is an eye condition that causes abnormal growth of fibrous tissue on the sclera. Pterygium could cause vision impairment when it reaches the area that blocks the pupil. Though the cause is still inconclusive, pterygium is associated with older age and male gender. The incidence of pterygium in Yogyakarta remains relatively unreported due to little documentation. This study aimed to report findings from the Pterygium Surgery Social Service Program, focusing on the age and sex distribution from several communities in Gunung Kidul, Yogyakarta. This study was a descriptive cross-sectional study. Study subjects were pterygium patients from the social service program organized by the Department of Ophthalmology, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, in October 2018 – March 2020. There were 227 patients consisted of 151 female patients (66.5%) and 76 male patients (33.5%). There were 22 patients (9.7%) who had grade I pterygium, 137 patients (60.4%) had grade II pterygium, 45 patients (19.8%) diagnosed as having third-grade pterygium, and 23 patients (10.1%) had grade IV pterygium. On average, female patients made a higher proportion of those having pterygium in all grades. The majority of patients in all age groups fell into second-grade pterygium, except for those aged >70 years old who had a higher number of those in the grade III category. In conclusion, female subjects made a higher proportion than males in all pterygium grades, and those aged 70 years and older had a more severe stage.